2004
DOI: 10.1111/j.1472-8206.2004.00296.x
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial infarction non‐invasively induced in rabbits by administering isoproterenol and vasopressin: protective effects exerted by verapamil†

Abstract: Myocardial infarction is usually induced in small animals by means of invasive procedures: the aim of this study was to cause heart necrosis lesions by non-invasive means. We injected rabbits with isoproterenol (3 mg/kg, i.p.) and vasopressin (0.3 mg/kg/5 min, i.v.) alone and in combination, and studied their effects on myocardial histology, electrocardiographic profiles, the appearance of the plasma cardiac necrosis marker c-troponin I (c-TPN I), hemodynamic parameters (blood pressure, heart rate), the coagul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 52 publications
2
16
0
Order By: Relevance
“…These results suggested that in the cynomolgus monkey, TnT and TnI distribution was from humans, mice, and rats as reported by Wallace et al (2004). Pinelli et al (2004) reported that myocardial injury in rabbits induced by administration of ISO + VASO (3 + 0.3 mg/kg) was characterized by necrosis of cardiac muscle, -dial infarction in humans. It has been reported that ISO, -traction and induces tachycardia, and that VASO, an anti- T max and C max were calculated for ASAT, ALAT, LDH, CPK, and ALD for each animal, and the mean level ± S.D.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…These results suggested that in the cynomolgus monkey, TnT and TnI distribution was from humans, mice, and rats as reported by Wallace et al (2004). Pinelli et al (2004) reported that myocardial injury in rabbits induced by administration of ISO + VASO (3 + 0.3 mg/kg) was characterized by necrosis of cardiac muscle, -dial infarction in humans. It has been reported that ISO, -traction and induces tachycardia, and that VASO, an anti- T max and C max were calculated for ASAT, ALAT, LDH, CPK, and ALD for each animal, and the mean level ± S.D.…”
Section: Discussionsupporting
confidence: 63%
“…34 No. 6 diuretic hormone, increases blood pressure by increasconsidered to induce ischemic myocardial injury by heart overload from increases in myocardial contraction and blood pressure (Pinelli et al, 2004). We administered ISO + VASO to cynomolgus monkeys, and investigated chronological changes in biomarkers, the relationship between those biomarkers and the severity of morphological myocardial injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, verapamil exerts protection against myocardial lesions, electrocardiographic alterations, high plasma cardiac necrosis marker c-troponin I levels, and prevents the hemodynamic and procoagulation changes. Therefore verapamil seems to be suitable for preventing myocardial ischaemic lesions induced by ISO and vasopressin [Pinelli et al 2004]. Nimodipine is used in the management of patients with stroke or subarachnoid haemorrhage [Towart and Kazda, 1979].…”
Section: Calcium Antagonistsmentioning
confidence: 99%
“…Positive inotropic agents which enhance cardiac force via increasing the intracellular Ca 2+ -concentration are disadvantageous because they may induce a Ca 2+ -overload of the cells, possibly followed by apoptosis (i.e. a programmed cell cycle which ends in the death of the cells [1], necrosis [2] and/or the development of tachycardia and arrhythmia [3]). In addition, the Ca 2+ -dependent increase in contractility is linked to increased cardiac energy/ATP and O 2 -consumption, which may be detrimental in situations where the oxygen supply of the heart is already limited.…”
Section: Introductionmentioning
confidence: 99%